Investigation of intestinal helminthes obtained from wild canids in Mongolia : Its materials, methods and preliminary results - 紀, 俊明; Chuluunbaatar, Gantigmaa; Sumiya, Battulga; Davaajav, Abmed; Davaasuren, Anu; 岡本, 宗裕; 柳田, 哲矢; 伊藤, 亮; 浅川, 満彦; ASAKAWA, Mitsuhiko (三恵社, 2013)
Book chapter モンゴル国では野生イヌ科動物のEchinococcus属条虫成虫を含む消化管寄生性蠕虫類の侵淫状況の調査がなされていなかった。その理由は、野生哺乳類の蠕虫研究自体が、当該国の研究者により実施されていないことと、海外研究者も関心を寄せなかったことが大きな理由とされている。腸絨毛に類似した2ないし3㎜程度のEchinococcus属条虫を大量の腸内容物から分別するには、適切な検出方法の手法が必要となる。そこで、国際貢献の一環として、検査作業方法の技術移転を兼ね、捕獲動物のサンプルを用い蠕虫検査の指導を行った。虫種確認は肉眼と実体・光学顕微鏡で実施した。用いたサンプルは当該国内数カ所で毛皮原料を得る目的で銃猟されたタイリクオオカミ Canis lupus、コサックギツネ Vulpes corsacおよびアカギツネV. vulpesの3種計420個体分の内臓および消化管であった。その結果、Echinococcus属はオオカミから単包条虫E. granulosusが、また、アカギツネから多包条虫 E. multilocularisがそれぞれ見つかった(Ito et al., 2013)。ほかの蠕虫としては、条虫 Taenia (おそらく、胞状条虫 T. hydatigena)、瓜実条(犬条虫)、Dipilidium caninum, Mesocestoides sp.、吸虫 Alaria sp.、鉤頭虫 Macracanthorhynchus sp.、線虫 Toxocara sp.、Ancylostoma sp.、Rictularia sp.が見出された。さらに興味深い事例として、ウマバエ類 Gasterophilus sp.、幼虫がキツネ類の腸内容物から見つかったことである。おそらく、斃死したウマの胃を食べた固体か、あるいはウマの糞と共に排出されたものを食べた事による偽寄生であろう。これまでの検出された蠕虫は、すでに欧州や中近東のオオカミで報告されているものと大きく異なることはないものの、モンゴル国では初めての記録であった。 There is no data on intestinal helminths including the genus Echinococcus in wild canids in Mongolia. So, the direct evidence of infections of the genus in the definitive host animals in Mongolia at least. Through our network with hunters and others, we could finally examine these animal intestines in Ulaanbaatar. A total of 420 individuals including wolves, corsac and red foxes were examined for detection of the helminths from small intestines. Among them, E. granulosus was obtained from wolves, and E. multilocularis was obtained from red foxes, respectively (Ito et al., 2013). Furthermore, the other helminths including Taenia hydatigena, Dipilidium caninum, Mesocestoides sp., Alaria sp., Macracanthorhynchus sp., Toxocara sp., Ancylostoma sp., Rictularia sp. etc. were detected. And, a larva of Gasterophilus sp. was found. Probably, this case was pseudoparasitism due to eating a horse stomach. 寄生虫学研究 2013年版 (浅川満彦編) book